1986
DOI: 10.1007/bf00180837
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine and pimozide alter reinforcement efficacy and motor performance

Abstract: This study evaluated the effects of chlorpromazine and pimozide on reinforced responding. In each session, rats were exposed to a series of five variable-interval reinforcement schedules. The response requirement was a lever press, the reward was a small portion of water, and the reinforcement rate varied from about 20 to 660 reinforcers per hour. Response rate was a negatively accelerated function of reinforcement rate, and the relationship between the two variables was described by the equation for a rectang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…This within-session procedure has produced 66 BACKGROUND REINFORCEMENT reliable results in previous studies of environmental (Bradshaw, Szabadi, & Bevan, 1976Heyman & Monaghan, 1987;Petry & Heyman, 1994) and pharmacological (Hamilton, Stellar, & Hart, 1985;Heyman, 1983Heyman, , 1992Heyman, Kinzie, & Seiden, 1986) manipulations of reinforcement efficacy.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…This within-session procedure has produced 66 BACKGROUND REINFORCEMENT reliable results in previous studies of environmental (Bradshaw, Szabadi, & Bevan, 1976Heyman & Monaghan, 1987;Petry & Heyman, 1994) and pharmacological (Hamilton, Stellar, & Hart, 1985;Heyman, 1983Heyman, , 1992Heyman, Kinzie, & Seiden, 1986) manipulations of reinforcement efficacy.…”
mentioning
confidence: 62%
“…However, this procedure has been used in numerous studies in a variety of contexts with an ascending order of VI schedules (Heyman, 1983;Petry & Heyman, 1994), a descending order (Heyman, 1983), a random order (Heyman et al, 1986;Heyman & Monaghan, 1987), and an ascending and then descending order (Heyman, 1992). In each case, response rates have varied in accord with the obtained rates of reinforcement in an orderly manner.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of cortical dopamine neurons discriminates between two reinforcement alternatives and reflects an animal's preference in a choice setting, suggesting that these neurons process the relative value of reinforcement [40,41]. Developmental MeHg exposure alters the synaptosomal uptake of dopamine [3], dopamine transmitter levels and turnover [3,4], and reduces monoamine oxidase (MAO) activity [7], alterations that may increase synaptic dopamine levels and thereby increase reinforcer efficacy [15,44]. These synaptic effects are reflected in elevated sensitivity of the behaving animal to acute doses of amphetamine in young rats [12,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, Belke (1997) showed that both localleverpressing and wheel-running rates increased throughout the session in rats responding on a tandem FR 1 VI 30-sec schedule for the opportunity to run. Belke (1996) found that wheel-running rates during 60-sec reinforcement peri- Note-For the Heyman, Kinzie, and Seiden (1986) and the Heyman and Monaghan (1987) studies, medians and ranges, rather than means and standard deviations, are reported. For studies using access to a running wheel as a reinforcer, the schedules were tandem FR I variable interval reinforcement schedules.…”
Section: Discussionmentioning
confidence: 99%